Enhancing Kindergarten Teachers’ Competence in Detecting and Managing Emotional and Behavioral Disorders in Early Childhood through Guidance and Counseling Training - Ainah, Noor Ainah; Sari, Nina Permata; Zahidah, Asih Nor; Syammari, Shoofii Syammari; Rofifah, Hani Nur (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Emotional and behavioural problems in early childhood are often overlooked, even though they can hinder children’s overall development. Kindergarten teachers play a vital role in identifying such issues and providing appropriate support. This community service project aimed to strengthen the competencies of teachers at TKITQ Bakkah Martapura through a one-day participatory training in guidance and counselling. The method involved pre-test, material presentation, group discussions, simulations, and post-test. The results revealed a significant improvement, with the average score increasing from 62.18 in the pre-test to 74.50 in the post-test. Beyond the numbers, teachers reported greater confidence in using simple tools for early detection as well as a better understanding of preventive and intervention strategies. In conclusion, a short yet practical training can have a meaningful impact on teachers’ competence. Nevertheless, ongoing support and follow-up programs are essential to ensure that the skills gained are consistently applied in classroom practice.